Budaya dan Sistem Kekeluargaan Etnis Aneuk Jamee - Julianti Sahputri, Budi Agustono & Fikarwin Zuska (Hukum Keluarga Islam IAIN LANGSA, 2021)
The Aneuk Jamee tribe is an acculturation of the Acehnese and Minangkabau tribes, both of which seem to have merged into one individual to produce a new ethnicity. This ethnicity later developed in South Aceh and influenced various aspects of culture and the family system in it. This research is classified as field research with a qualitative approach. The methodology used is phenomenology which is supported by historical literacy in the South Aceh region where the Aneuk Jamee ethnicity is the most dominant. Informants in this study consisted of primary and secondary sources, the primary sources were individuals or native Aneuk Jamee selected by random sampling. The secondary sources are informants who are not native to Aneuk Jamee but have insight and knowledge regarding the history and customs of Aneuk Jamee. The results of the study concluded that the Aneuk Jamee community has similarities with the system in the Minangkabau community in West Sumatra, namely adopting a hereditary system from the mother's side or commonly referred to as Matrilineal. Even though there has been Islamization in Aceh where the father is a descendant of the lineage, the matrilineal system is still evident in kinship (household) matters. All matters that will be carried out in a household must be discussed in advance with the ninik mamak (mother's brother).